2018
DOI: 10.1080/19371918.2017.1415179
|View full text |Cite
|
Sign up to set email alerts
|

Suicidality and Other Health Risk Behaviors among Female Youth in Juvenile Detention

Abstract: This study investigates suicidality and health-risk behaviors among female juvenile detainees and identifies the extent to which suicidal behaviors are correlated with other risky activities. This study also explores 12 health risk behaviors, their prevalence, and relative associations to suicidal behaviors within the sample-population. Researchers collected data from 104 female adolescents, ages 12 to 20, residing in a long-term, detention center in the southeastern region of the United States. Descriptive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Similarly, a recent study demonstrated that nongender-conforming high school students were much more likely to report engagement in self-harming activities and risky alcohol use behaviors, particularly among males than students identifying as heterosexual (Goodin et al, 2019; Reisner et al, 2014). A higher rate of suicide attempts and/or suicidal ideation was reported among other vulnerable subgroups, including Latinx (Price & Khubchandani, 2017), female juvenile detainees (Hatcher et al, 2018), Black welfare children (Heneghan et al, 2013), females in early high school years (Rew et al, 2016), and military dependents (Pressley et al, 2012).…”
Section: Resultsmentioning
confidence: 98%
“…Similarly, a recent study demonstrated that nongender-conforming high school students were much more likely to report engagement in self-harming activities and risky alcohol use behaviors, particularly among males than students identifying as heterosexual (Goodin et al, 2019; Reisner et al, 2014). A higher rate of suicide attempts and/or suicidal ideation was reported among other vulnerable subgroups, including Latinx (Price & Khubchandani, 2017), female juvenile detainees (Hatcher et al, 2018), Black welfare children (Heneghan et al, 2013), females in early high school years (Rew et al, 2016), and military dependents (Pressley et al, 2012).…”
Section: Resultsmentioning
confidence: 98%
“…Compared to girls in the general population, justice-involved girls experience earlier sexual debut, higher rates of sexual activity, and higher numbers of lifetime partners (Biswas & Vaughn, 2011;Braverman, 2011;Dembo, Belenko, Childs, Greenbaum, & Wareham, 2010;Dembo et al, 2017;Gallagher, Dobrin, & Douds, 2007;Golzari, Hunt, & Anoshiravani, 2006;Hatcher, King, Nordberg, Bryant, & Woolen, 2018;Kaplan et al, 2001;Kelly, Morgan-Kidd, Champion, & Wood, 2003;Morris et al, 1995;Odgers, Robins, & Russell, 2010;Rizk & Alderman, 2012). Other risks are also prevalent in studies with justiceinvolved samples: One study reported that 19% of detained girls (n = 197) disclosed exchanging sex for money or drugs within the previous two months (Crosby et al, 2004).…”
Section: Sexual and Reproductive Health (Srh) Needs Of Justice-involvmentioning
confidence: 99%